Farelo de arroz desengordurado e farelo de glúten de milho na suplementação de bovinos de corte - Leite, Daniel Terra (2006)
Three experiments were developed to test the effect of the supplementation with defated rice bran (FAD), corn gluten feed (FGM) and their mixture, on steers performance. The field tests were at the Experimental Farm "Area Nova", and the laboratorial analyses at the Animal Nutrition Laboratory - LANA, both pertaining to the Department of Animal Science of the Universidade Federal de Santa Maria - UFSM, Santa Maria city, state of Rio Grande do Sul. Twenty-four steers with average age of 15 months and live weight 210 kg, cross Nelore x Charolais, that had as diet base, pasture of sorgo AG2501® variety grazing (Sorghum bicolor (L.) Moench) whe the steers remained four daily hours in the mourning. The animals were distributed at the following experiments: 1) levels of supplementation with FGM, 2) levels of supplementation with FAD and 3) levels of substitution of FGM per FAD in the supplement composition. The quantitative parameters of the pasture, the ingested forrage and supplements quality, and the performance of the animals were evaluated. The total dry matter intake was determined by the indirect fecal production estimate, using a external marker (Chromium Oxide). The FGM increased the daily average weight gain with the increase of the supplementation level in relation to the live weight. The FAD can be used as supplementation approximately 0.40% of the animals live weight; levels above of these can harm the bovines development. The mixture of the two supplements did not influence the animals performance.